KONSTRUKSI PEMBERITAAN PELECEHAN SEKSUAL PADA MEDIA ONLINE DETIK.COM DAN TRIBUNNEWS.COM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study, entitled "Construction of Sexual Harassment Reporting on Detik.com and Tribunnews.com Online Media" the research aims to 1) find out the online media Detik.com and Tribunnews.com to extrude news of sexual harassment to the Agni case, UGM student through framing analysis, and 2 ) to determine the trend in the position of the two online media. This type of research is descriptive qualitative research. Descriptive qualitative is describing or finding facts with the correct interpretation. This analysis uses the Robert N Entman model, there are four elements, namely: 1) problem identification, 2) causal interpretation, 3) making moral decisions (moral evaluation), 4) solutions to problems (treatment recommendation). The results of the research show that 1) Detik.com online media framed news by publishing a series of UGM student responses, while online media Tribunnews.com framed the news as not transparent to the Agni case and called Agni a salted fish 2) Tribunnews.com framed the news with a highlight in solving the Agni case problem to the campus who plays the role of wanting to solve it in an academic way and provides psychological counseling for both students. Meanwhile, Detik.com explained Agni's case by displaying pressure from the #kitaAgni movement that wanted to bring the case to the realm of law. It can be seen that Tribunnews.com media sided with the campus and Detik.com media sided with UGM students and survivors.